Cellular Toxicity of Calf Blood Extract on Human Corneal Epithelial Cells In Vitro. (January 2015) - Park, Young Min; Kim, Su Jin; Han, Young Sang; Lee, Jong Soo
Abstract Purpose: To investigate the biologic effects of the calf blood extract on corneal epithelial cells in vitro. Materials and methods: The effects on corneal epithelial cells were evaluated after 1, 4, 12, and 24 h of exposure to various concentrations of calf blood extract (3, 5, 8 and 16%). The MTT (3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyl tetrazolium bromide) assay was performed to measure levels of cellular metabolic activity. The lactate dehydrogenase (LDH) assay was performed to determine the extent of cellular damage. Cellular morphology was examined using phase-contrast microscopy. The scratch wound assay was performed to quantify the migration of corneal epithelial cells. Results: At the 3 and 5% concentrations of calf blood extract, MTT values were similar to those observed in the control group. However, at a concentration of 8 and 16%, cellular metabolic activity was significantly decreased after 4 h of exposure to calf blood extract. After 12 h of exposure to 8 and 16% concentrations of calf blood extract, LDH activity and cellular morphological damage to the corneal epithelial cells were significantly increased. There was no evidence of cellular migration after 12 h exposure to 5% or higher concentration of calf blood extract because of cellular toxicity. Conclusions: Compared with normal corneal epithelial cells, the cellular activity was decreased, and toxicity was increased after over 12 h of exposure to more than 5% concentration of calf blood extract. Further clinical studies will be necessary to determine the optimal concentration and exposure time for the topical application of eye drops containing calf blood extract.